2016
DOI: 10.1155/2016/1796357
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Dependent Effects of Dietary Genistein on Echocardiographic Profile and Cardiac GLUT4 Signaling in Mice

Abstract: This study aimed to determine whether genistein diet resulted in changes in cardiac function, using echocardiography, and expression of key proteins involved in glucose uptake by the myocardium. Intact male and female C57BL/6J mice (aged 4–6 weeks) were fed either 600 mg genistein/kg diet (600 G) or 0 mg genistein/kg diet (0 G) for 4 weeks. Echocardiography data revealed sex-dependent differences in the absence of genistein: compared to females, hearts from males exhibited increased systolic left ventricle int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…Similar values in healthy and MetS + Sd + SAE and MetS + HFd + SAE group suggest that Aronia extract was capable of improving fractional shortening during both high-calorie and standard dietary conditions in the presence of metabolic syndrome. In accordance with our findings, it has been previously reported that polyphenolics and plants rich in polyphenolics had effect in lessening the pathological alterations in FS promoted by MetS [27,28,29]. A decrease in systemic blood pressure after Aronia extract treatment may increase fractional shortenings, resulting in increased myocardial contractility [30].…”
Section: Discussionsupporting
confidence: 91%
“…Similar values in healthy and MetS + Sd + SAE and MetS + HFd + SAE group suggest that Aronia extract was capable of improving fractional shortening during both high-calorie and standard dietary conditions in the presence of metabolic syndrome. In accordance with our findings, it has been previously reported that polyphenolics and plants rich in polyphenolics had effect in lessening the pathological alterations in FS promoted by MetS [27,28,29]. A decrease in systemic blood pressure after Aronia extract treatment may increase fractional shortenings, resulting in increased myocardial contractility [30].…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with previous findings showing that natural substances belonging to a group of flavonoids might ameliorate endothelial dysfunction and cardiac hypertrophy in the spontaneously hypertensive rats [26, 27]. Additionally, the beneficial effect of isoflavones on overall cardiovascular markers in models of LV dysfunction, involving enhancement of percent FS, has been proven so far [28].…”
Section: Discussionsupporting
confidence: 91%
“…Subcutaneous genistein administration of 0.2 mg/kg/day in ovariectomized New Zealand white female rabbits did not have a protection efect on ischemic myocardium in both nonovariectomized or ovariectomized animals for 4 weeks [35]. Compared to control groups, genistein treatment (600 mg/kg, diet) for 4 weeks in both sexes of C57BL/6J mice made echocardiographic changes in function, increased left ventricle internal dimension (LVIDs), cardiac GLUT4 protein expression, and signifcantly decreased fractional shortening and whole heart surface area [36].…”
Section: In Vivo Studiesmentioning
confidence: 88%